Symposium 7: Where’s the "I" in communities of inquiry? Symposium Introduction - Deepwell, Frances (Proceedings of the International Conference on Networked Learning, 2006)
Within this symposium, colleagues from one institution explore a range of issues that are challenging a newly emerging community of inquiry, namely the iPED research network at Coventry University. The research network was established in 2005 in order to strengthen the pedagogical research capacity within Coventry University at a time when disciplinary research is being supported only in a limited number of subject areas. It is envisaged that the pedagogical research activity will drive up professional standards in teaching practice by promoting reflective and evaluative approaches to curriculum development and delivery. The initiative is spearheaded by three half-time research fellows and educational researchers based in the Centre for Higher Education Development. The network aims to be inclusive of a range of pedagogical approaches and research methodologies, however there are core inter-connected themes, such as: research-led learning, work-based learning, scenario-based learning, realistic work environments, writing in the disciplines and e-learning. The iPED research network builds upon a previous large-scale capacity-building initiative at the University where the focus was on innovative practices. The previous initiative, the teaching, learning and assessment taskforce, developed a community of practice in innovatory practice (Deepwell & Beaty, 2005) which was perceived internally to have enjoyed only moderate success. One of the reasons for this was the relatively low research output from the activities. However, there were many other tangible and long-term gains to the institution and to the individuals from involvement in the taskforce community. This community helped to define the online learning environment that has become deeply embedded within the culture of the organisation. There are similar hopes that the new research network will influence practice across the university. As the research network gets under way, it is interesting to record what is emerging at periodic intervals so that the development of the community can be charted. This transition phase lies at the heart of the present symposium. The assemblage of papers represents different elements of the iPED research network. Each one, in its own way, explores discrete themes, however, we have attempted to draw these together into a coherent set of papers which explore notions of identity and identification. The first paper by Clouder critically appraises how a disparate community of researchers into work-based learning are developing as a community of practice, and learning to manage online sensibilities as they shape an identity for themselves. In the second paper, King uses situational analysis to explore the online pedagogies of scenario-based learning and the implications of this for tutor and learner identity. The third paper by Courtney, Deepwell & Turner provides a force field analysis of an educational development team redefining itself within a research group.